PENGARUH BRAND EQUITY TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN THRIFT SHOPPING PADA MAHASISWA UNIVERSITAS ABDURACHMAN SALEH SITUBONDO - Sari, Rini Kartika; Sari, Lita Permata (Relawan Jurnal Indonesia, 2023)
The development of the fashion industry is undergoing a rapid increase, even fashion trends can change every monthly period. Existing information technologies are becoming a means of conveying information about changes in current fashion trends, which can influence different points of view and opinions about dressing in appearance. Everyone has a different lifestyle or distinctive features of each in appearance. The existence of Thrift shopping is one of the alternative ways of the fashion world through the purchase of used clothes. The emergence of this second-hand item, becomes an opportunity for teenagers who want to remain fashionable but at a minimum price, so that it is accessible to teenagers. This study is descriptive with a quantitative approach to prove the existing hypothesis regarding the influence of Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty on thrift shopping purchase decisions in students at Abdurachman Saleh Situbondo University. Based on the results of the F (simultaneous) Test study, which showed a significant value of 0.000 is below 5%. This means that Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty influence students to behave thrift shopping in students at Abdurachman Saleh Situbondo University. Test t (partial), Brand Awareness, Brand Association, Perceived Quality, and Brand Loyalty had a positive and significant effect on thrift shopping purchase decisions in students at Abdurachman Saleh Situbondo University.